Inhibiting the proton pump: mechanisms, benefits, harms, and questions - Aronson, J (BioMed Central, 2016)
Inhibition of the H+/K+-adenosine triphosphatase (the proton pump) is the final common mechanistic pathway in reducing gastric acid secretion pharmacologically. Proton pump inhibitors are widely used in upper gastrointestinal diseases, including gastric and duodenal ulcers, eradication of Helicobacter pylori in combination with antibiotics, gastroesophageal reflux disease, Zollinger-Ellison syndrome, eosinophilic esophagitis, and prevention of non-steroidal anti-inflammatory drug-induced peptic ulceration. Reviewing their benefits and harms in BMC Medicine, Scarpignato et al. report effectiveness in these conditions, and harms that are generally mild and uncommon (1-3 %). Serious adverse reactions, such as tubulointerstitial nephritis, are rare. However, the risks of gastric and pancreatic cancer are unclear. Drug-drug interactions can occur through effects on P glycoprotein and cytochrome P450 (CYP) isoenzymes. Several questions remain. Do all proton pump inhibitors carry the same risks of serious adverse reactions? Which individuals are most susceptible? What are the time courses of individual reactions? What monitoring strategies are best? New drugs for the same indications continue to emerge, including potassium-competitive acid blockers, inhibitors of transient lower esophageal sphincter relaxation, serotonergic agents/prokinetics, mucosal protectants, histamine H3 receptor agonists, anti-gastrin agents, and esophageal pain modulators. Their benefit to harm balance remains to be discovered.Please see related article: https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-016-0718-z.